3D printing of microfluidic chips: evaluation of printing using FDM - Ho,Thaddaeus Shao Yong (Nanyang Technological University, 2024)
The growing popularity of 3D printing has made 3D printers more affordable and accessible to the public, allowing for a massive improvement in the manufacturing process and complementing the developments of Industry 4.0. With the advancement of 3D printing in microfluidic devices, it has simplified current manufacturing processes and facilitates the customisation of microfluidics’ channel design. As well as the growth of developing microfluidics integrated with biosensors. This project explores the possibility of using an extrusion-based 3D printing method to print a simple mixer with closed channel geometry in the planar and non-planar orientation. By quantifying the accuracy and precision of the printed microfluidics’ channel. The mixing efficiency and fluid flow inside the microfluidic is demonstrated through Image colour analysis and light absorbance test. Results showed promising potential in fabricating planar and non-planar channel structure with channel’s diameter as small as 500µm. Furthermore, with the design of a non-planar orientation channel structure which have abrupt changes in direction, improves mixing uniformity of inlet samples.